Yield performance of aromatic fine rice as influenced by integrated use of vermicompost and inorganic fertilizers - Laila, Nowshin; Sarkar, Md. Abdur Rahman; Paul, Swapan Kumar; Rahman, Afrina (Journal of the Bangladesh Agricultural University, 2024)
Yield performance of various aromatic rice varieties needed to be assessed by different nutrient management practices before promoting a suitable integrated nutrient management for aromatic rice production in Bangladesh. Therefore, an experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during July 2017 to December 2017 to study the combined effect of vermicompost with inorganic fertilizers on the yield and yield contributing characters of aromatic fine rice varieties. The experiment comprised three varieties viz. BRRI dhan34, Binadhan-13 and Kalizira and five nutrient managements viz. control (no application of manures and fertilizer), recommended dose of inorganic fertilizers ( i.e. 150, 95, 70, 60, 12 kg ha-1 of Urea, TSP, MOP, Gypsum and Zinc Sulphate respectively), ermicompost @ 3 t ha-1, 25% less than recommended dose of inorganic fertilizer + vermicompost @ 1.5 t ha-1, 50 % less than recommended dose of inorganic fertilizer + vermicompost @ 3 t ha-1. The experiment was laid out in a randomized complete block design with three replications. Result showed that, yield and yield components of aromatic fine rice were significantly influenced by variety, nutrient management and interaction of variety and nutrient management. In case of variety, the highest and the lowest value of grain yield (3.89, 2.80 t ha-1) and straw yield (5.29, 4.03 t ha-1) were found in Binadhan-13 and Kalizira, respectively. In case of nutrient managements, the highest yield and yield component were obtained from 50% less than the recommended dose of inorganic fertilizers + vermicompost @ 3 t ha-1 treatment. The highest number of total tillers hill-1, effective tillers hill-1, number of grains panicle-1, panicle length, grain yield (4.04 t ha-1) and straw yield (6.20 t ha-1) were obtained from the interaction of Binadhan-13 and 50% less than the recommended dose of inorganic fertilizers + vermicompost @ 3 t ha-1. The lowest values related to yield were found in Kalizira with control condition. Binadhan- 13 along with 50% less than the recommended dose of inorganic fertilizers + vermicompost @ 3 t ha-1 might be a promising practice for aromatic fine rice cultivation. J Bangladesh Agril Univ 18(2): 260–265, 2020 https://doi.org/10.5455/JBAU.90309